Combination of nanotechnology with vascular targeting agents for effective cancer therapy. Issue 4 (23rd August 2017) - Jahanban‐Esfahlan, Rana; Seidi, Khaled; Banimohamad‐Shotorbani, Behnaz; Jahanban‐Esfahlan, Ali; Yousefi, Bahman
Abstract : As a young science, nanotechnology promptly integrated into the current oncology practice. Accordingly, various nanostructure particles were developed to reduce drug toxicity and allow the targeted delivery of various diagnostic and therapeutic compounds to the cancer cells. New sophisticated nanosystems constantly emerge to improve the performance of current anticancer modalities. Targeting tumor vasculature is an attractive strategy to fight cancer. Though the idea was swiftly furthered from basic science to the clinic, targeting tumor vasculature had a limited potential in patients, where tumors relapse due to the development of multiple drug resistance and metastasis. The aim of this review is to discuss the advantages of nanosystem incorporation with various vascular targeting agents, including (i) endogen anti‐angiogenic agents; (ii) inhibitors of angiogenesis‐related growth factors; (iii) inhibitors of tyrosine kinase receptors; (iv) inhibitors of angiogenesis‐related signaling pathways; (v) inhibitors of tumor endothelial cell‐associated markers; and (vi) tumor vascular disrupting agents. We also review the efficacy of nanostructures as natural vascular targeting agents. The efficacy of each approach in cancer therapy is further discussed. Abstract : Various nanostructure particles were developed to reduce drug toxicity and allow the targeted delivery of various diagnostic and therapeutic compounds to the cancer cells. Targeting tumor vasculature rather than tumor cells is an appealing strategy, since cutting off the tumor‐feeding system would lead to the indirect targeting of tumor cells, as well.